The Investigation Of Translation Shifts In “Monster Pets: A Hotel Transylvania Short Film” - Muhammad Rayhan Ramadhan; Nurma Dhona Handayani (International Journal of Social Welfare and Family Law, 2025)
This research identified the types of translation shifts in “Monster Pets: A Hotel Transylvania Short Film”. Qualitative research was employed as the research design. The data were collected using the observational method by (Sudaryanto, 2015) where the researchers closely observed and compared the original and translated versions of "Monster Pets: A Hotel Transylvania Short Film" to identify translation shifts. The data of translation shifts were analyzed using (Catford, 1965) theory of translation shifts. Finally, the outcome of this research were descriptive qualitative study. Through the analysis, three types of translation shifts were identified: level shifts, structure shifts, and unit shifts. A total of 16 data of translation shifts were examined, which included 1 data of level shifts, 8 data of structure shifts, and 7 data of unit shifts. Among the three types of shifts, structure shifts were the most dominant, indicated that changes in the grammatical structure were the most frequent translation strategy employed in adapting the dialogue from English to Indonesian. The findings highlighted the importance of structure shifts in the translation process of this particular source material.